Plasma metabolic profiling on postoperative colorectal cancer patients with different traditional Chinese medicine syndromes. (February 2018) - Hu, Xue-Qing; Wei, Bin; Song, Ya-Nan; Ji, Qing; Li, Qi; Luo, Yun-Quan; Wang, Wen-Hai; Su, Shi-Bing
Highlights: Plasma metabolic profiles of PCRC patients were perturbed. Increased levels of terephthalic acid may indicate higher risk of relapse. Creatinine and aminomalonic acid alternation may involve in the formation of Dampness and heat syndrome, whiled -tryptophan may associate with Spleen deficiency syndrome andd -galactose and 1, 2, 3-propanetricarboxylic acid may relate to Liver and kidney Yin deficiency syndrome. As numbers of patients in each TCM syndrome are small, further study is needed to verify those results. Abstract: Objectives: This study aims to investigate the metabolic profiles of postoperative colorectal cancer (PCRC) patients with different traditional Chinese medicine (TCM) syndromes and to discuss the metabolic mechanism under PCRC progression and TCM syndrome classification. Methods: Fifty healthy controls (HC) and 70 PCRC patients, including 10 Dampness and heat syndrome (DHS), 33 Spleen deficiency syndrome (SDS), 19 Liver and kidney Yin deficiency syndrome (LKYDS) and 8 with non-TCM syndrome (NS) were enrolled. Plasma metabolic profiles were detected by Gas chromatography-mass spectrometry (GC–MS) and analyzed by principal component analysis (PCA) and partial least squares-discriminate analysis (PLS-DA). Furthermore, pathway enrichment was analyzed based on KEGG and DAVID databases and metabolic network was constructed via metaboanalyst and cytoscape. Results: The top-3 metabolites with higher abundance in PCRC compared with HC were terephthalic acid (165.417-fold), ornithine (24.484-fold) and aminomalonic acid (21.346-fold). And the cholesterol (0.588-fold) level was decreased in PCRC.l -Alanine, 1, 2-ethanediamine, urea, glycerol, glycine, aminomalonic acid, creatinine and palmitic acid were specifically altered in the DHS, whiled -tryptophan was exclusively changed in SDS, andl -proline, 1, 2, 3-propanetricarboxylic acid, d -galactose and 2-indolecarboxylic acids in LKYDS. Conclusions: The plasma metabolic profiles were perturbed in PCRC patients. Increased levels of terephthalic acid might indicate high risk of relapse and elevated ornithine may contribute to the post-operational recovery or may raise the susceptibility to PCRC recurrence. The metabolic profiles of DHS, SDS, LKYDS and NS were almost separately clustered, indicating the possibility of explaining TCM syndromes classification using metabolomics. Furthermore, creatinine and aminomalonic acid alternation might correlate with the formation of DHS, whiled -tryptophan may associate with SDS andd -galactose and 1, 2, 3-propanetricarboxylic acid may relate to LKYDS. As numbers of patients in each TCM syndrome are small, further study is needed to verify those results.